Pengaruh Bauran Pemasaran Terhadap Kepuasan Pelanggan Pada Toko Baju Muslim Kota Kendari - Andi Azwar Anas Idris (LP3M Universitas Muhammadiyah Kendari, 2023)
This study investigates the impact of marketing factors on the level of customer satisfaction in X Kendari Muslim fashion store. The results of the analysis show that products have a positive and significant influence on customer satisfaction. Higher product quality contributes to increased customer satisfaction. In addition, price also has an important impact; when the price matches the value of the product, customer satisfaction increases. Store location also plays a crucial role in customer satisfaction. Strategically located stores result in greater satisfaction. Promotion also has a significant positive influence, with the implementation of good promotions able to increase customer satisfaction.